(3cJGH GdbUO Edi Gddg JYGdis - (3GdLfjO Hf eMeO Hf GdLfjO GdHZOGOj GdNRGR, CHh GdbGSe , J (B297 (3g` s
(3ChdgG (B:s
(3GdMeO ddg MeO ef bUO Edi Gdedc GdLhGO CeG HYO eYGTQ GdbGUOjf Edi ehGUdI Gddg JYGdi hbQHg acd ef bUO Gddg JYGdi hbUO ehGUdJg adG jNdhG ef EMOi KdGK s
(3BNQgG (B:s
(3CagehG eYGTQ GdbGUOjf Edi Gddg JYGdi eG PcQfG dce ef HjGf GdJgF ddbUO heG jfHZi dce ajg YHGO aVdhG HGdSQ MJi OfhG efg hUGQhG bGUOjfG Je cJGH GdbUO Edi Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJUha hGdBOGH GdTQYjIs